2006
DOI: 10.1213/01.ane.0000221452.72892.2c
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Subgluteal Sciatic Nerve Blocks with Stimulating Catheters in Children: A Descriptive Study

Abstract: We describe our clinical experience of combining ultrasound guidance and nerve stimulation for the insertion of subgluteal sciatic catheters in children. Ten children scheduled for lower limb surgery with a combined general anesthetic and a subgluteal sciatic catheter placement for both operative anesthesia and postoperative pain relief were studied. Under ultrasonographic guidance the sciatic catheter was placed using an 17-gauge 50-mm Arrow continuous peripheral nerve block needle and a 19-gauge stimulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(23 citation statements)
references
References 30 publications
0
20
0
3
Order By: Relevance
“…3 Recently, there has been an increase in interest in the use of ultrasound for peripheral nerve blocks, 4,5 including applications using the posterior approach to sciatic nerve block at the subgluteal level. 6,7 The results of a volunteer study showed that the sciatic nerve can be identified at the lesser trochanter level anteriorly, 8 where the anterior approach to the sciatic nerve block is also performed. However, no literature has adequately described successful use of the ultrasound-guided anterior approach to sciatic nerve block.…”
mentioning
confidence: 99%
“…3 Recently, there has been an increase in interest in the use of ultrasound for peripheral nerve blocks, 4,5 including applications using the posterior approach to sciatic nerve block at the subgluteal level. 6,7 The results of a volunteer study showed that the sciatic nerve can be identified at the lesser trochanter level anteriorly, 8 where the anterior approach to the sciatic nerve block is also performed. However, no literature has adequately described successful use of the ultrasound-guided anterior approach to sciatic nerve block.…”
mentioning
confidence: 99%
“…Ulaşabildiğimiz kataterli ilk çalışma Geffen ve arkadaşlarının yaptığı çalışmadır. Bu çalışmada USG ve NS konbinasyonu çocuklarda subgluteal siyatik kataterlerin yerleştiril-mesi için başarılı siyatik bloklar sağlamıştır [13].…”
Section: Discussionunclassified
“…Van Gef fen ve Geilen ayak cer ra hi si ge çi ren yaş la rı 2-14 ara sın da ki ço-cuk la ra ul tra son eş li ğin de sub glu te al ola rak si ya tik si nir ka te te ri yer leş tir miş ve hiç komp li kas yo na rastla ma dan mü kem mel pos to pe ra tif anal je zi sağ la dık -la rı nı be lirt miş ler dir. 2 Ço cuk lar da ul tra son kul la nı mı, si nir le rin da ha yü zey sel yer leş me si ve eriş kin ler den da ha faz la vü cut sı vı sı içer me si ne deniy le da ha ko lay ol mak ta ve da ha iyi gö rün tü vermek te dir. Pe ri fe rik si nir blo ğu ve ka te ter uy gu la ma sı, uyu yan ço cuk ta da ha ko lay ve da ha az komp li kas yon ya ra tır ken, USG kul la nı mı ile bu oran lar da ha da azal mak ta dır: Da mar içi ilaç ya pıl -ma sı ve ya si nir içi en jek si yon lar dan, lo kal anes te tik ajan en jek si yo nu ile do ku nun ge niş le me si gö rü le rek sa kı nı la bil mek te dir.…”
Section: Tar Tiş Maunclassified
“…Son za man lar da rej yo nel anes te zi, özel lik le pe ri ferik si nir blok la rı, ayak cer ra hi le rin de se çi len posto pe ra tif anal je zi yön tem le ri ol mak ta dır. 2,3 Di ğer pos to pe ra tif anal je zi tek nik le ri ara sın da, sis te mik opi o id kul la nı mı (has ta kon trol lü anal je zi) ve epidu ral ka te ter ile de vam lı anal je zi uy gu lan ma sı yer al mak ta dır. Epi du ral ka te ter den de vam lı anal je zi uy gu lan ma sı ve sis te mik opi o id uy gu la ma la rı nın bir çok yan et ki le ri nin ol du ğu bi lin mek te dir; bulan tı, kus ma, id rar re tan si yo nu, faz la se das yon, kaşın tı ve mo tor blok bun lar dan ba zı la rı dır.…”
unclassified